Privacy in peril - Rule, James B., 1943- (Oxford : Oxford University Press, 2007)
'Privacy in Peril' is the first book to look at the big picture of privacy-eroding trends, analyze their common roots, and anticipate their consequences.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Privacy, Right of; Privacy, Right of -- United States; Privacy, Right of -- Cross-cultural studies